2012
DOI: 10.1111/j.1538-7836.2012.04704.x
|View full text |Cite
|
Sign up to set email alerts
|

Superficial vein thrombosis and recurrent venous thromboembolism: a pooled analysis of two observational studies

Abstract: Summary.  Background:  The management strategies for symptomatic isolated superficial vein thrombosis (SVT) (without concomitant deep vein thrombosis [DVT] or pulmonary embolism [PE]) have yet to achieve widespread consensus. Concerns have been raised regarding the usefulness of prescribing anticoagulant treatments to all patients with isolated SVT. Determining the isolated SVT subgroups who have the highest risks of venous thromboembolism (VTE) recurrence (composite of DVT, PE, and new SVT) may facilitate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 23 publications
4
29
0
2
Order By: Relevance
“…Second, although these risks attenuate over time, they remain 3-to sixfold increased even after 5 years. Our findings are in accord with earlier studies showing VTE risks of 3% to 4% in the first 3 months after SVT 4,19 as well as a four-to sixfold increased long-term risk for deep venous events in patients with a history of SVT 7,8 and suggests that superficial and deep venous events result from a common hypercoagulable state. This thesis is supported by the finding that a DVT occurs in the contralateral leg in up to 10% of cases.…”
Section: Discussionsupporting
confidence: 93%
“…Second, although these risks attenuate over time, they remain 3-to sixfold increased even after 5 years. Our findings are in accord with earlier studies showing VTE risks of 3% to 4% in the first 3 months after SVT 4,19 as well as a four-to sixfold increased long-term risk for deep venous events in patients with a history of SVT 7,8 and suggests that superficial and deep venous events result from a common hypercoagulable state. This thesis is supported by the finding that a DVT occurs in the contralateral leg in up to 10% of cases.…”
Section: Discussionsupporting
confidence: 93%
“…7,16 During the last 3 decades, however, several studies have shown that it can be associated with a significant risk of thromboembolic complications, including deepvein thrombosis, pulmonary embolism, and extension or recurrence of the index event, even in patients receiving anticoagulant treatments. [2][3][4]12,17 Our study confirms these findings, with a 9.4% rate of such objectively confirmed symptomatic thromboembolic complications in untreated patients at day 77, including a 7.3% rate of symptomatic SVT extensions. These high rates were observed despite the exclusion of patients in the highest risk category for thromboembolic complications (such as those with active cancer or recent venous thromboembolism) from the CALISTO study, to avoid their potential exposure to treatment with a placebo.…”
Section: Discussionsupporting
confidence: 85%
“…In CALISTO, a cutoff value of 3 cm from the SFJ was chosen for defining SVT extension because most authors and consensus groups emphasize that extensions involving the SFJ are associated with an increased risk of thrombus propagation into the deep venous system. [7][8][9][10][11][12] However, few data are available describing the natural history of patients presenting with a SVT extension, whether this progressed to within <3 cm or to .3 cm from the SFJ, and the optimal therapeutic strategy to manage this complication remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…7 The low rate of anticoagulant use in our study may be related to the years studied (before guidelines supported fondaparinux), as well as being largely comprised of outpatients, and also because we included types of SVTE that are unlikely to progress to DVT, such as small vein phlebitis or upper extremity SVTE. 4,10 Limitations of our analysis include the heterogeneous types of SVTE included in our study and our reliance on available chart documentation to ascertain SVTE diagnosis, risk factors, and treatment. Because of the observational nature of our study, SVTE in the hospital setting may have been less well documented in medical records, leading to a sample of mostly outpatients.…”
Section: Discussionmentioning
confidence: 99%